The Accuracy of Plain Radiography in Detection of Traumatic Intrathoracic Injuries - Abedi Khorasgani, Maryam; Shahrami, Ali; Shojaee, Majid; Alimohammadi, Hossein; Amini, Afshin; Hatamabadi, Hamid Reza (Archives of Academic Emergency Medicine, 2018)
Introduction: Rapid diagnosis of traumatic intrathoracic injuries leads to improvement in patient management. This study was designed to evaluate the diagnostic value of chest radiography (CXR) in comparison to chest computed tomography (CT) scan in diagnosis of traumatic intrathoracic injuries. Methods: Participants of this prospective diagnostic accuracy study included multiple trauma patients over 15 years old with stable vital admitted to emergency department (ED) during one year. The correlation of CXR and CT scan findings in diagnosis of traumatic intrathoracic injuries was evaluated using SPSS 20. Screening characteristics of CXR were calculated with 95% CI. Results: 353 patients with the mean age of 35.2 ± 15.8 were evaluated (78.8% male). Age 16-30 years with 121 (34.2%), motorcycle riders with 104 (29.5%) cases and ISS < 12 with 185 (52.4%) had the highest frequency among patients. Generally, screening performance characteristics of chest in diagnosis of chest traumatic injuries were as follows: sensitivity 50.3 (95% CI: 44.8 – 55.5), specificity 98.9 (95% CI: 99.5 – 99.8), PPV 97.8 (95% CI: 91.5 – 99.6), NPV 66.4 (95% CI: 60.2 – 72.03), PLR 44.5 (95% CI: 11.3 175.3), and NLR 0.5 (95% CI: 0.4 – 0.6). Accuracy of CXR in diagnosis of traumatic intrathoracic injuries was 74.5 (95% CI: 69.6 – 78.9) and its area under the ROC curve was 74.6 (95% CI: 69.3 – 79.8). Conclusion: The screening performance characteristics of CXR in diagnosis of traumatic intrathoracic injuries were higher than 90% in all pathologies except pneumothorax (50.3%). It seems that this matter has a great impact on the general screening characteristics of the test (74.3% accuracy and 50.3%sensitivity). It seems that, plain CXR should be used as an initial screening tool more carefully.